2012
DOI: 10.2323/jgam.58.173
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of polyhydroxyalkanoates producing bacteria and biochemical characterization of their possible application

Abstract: Polyhydroxyalkanoates (PHAs) accumulating bacteria were isolated under various selective conditions such as pH, salt concentrations and types of heavy metal. Fifty strains of bacterial isolates were found to belong to Bacillus, Proteus, Pseudomonas, Aeromonas, Alcaligenes and Chromobacterium, based on phenotypical features and genotypic investigation. Only twenty fi ve bacterial isolates were selected and observed for the production of PHAs. Interestingly, bacteria belonging to Firmucutes Bacillus sp. produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 28 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…A number of Bacillus species, but not all, can accumulate PHA in their cells under unbalanced growth conditions. The Bacillus species reported as native producers of PHA are as follows: (Yilmaz et al 2005;Kaynar and Beyatli 2009;Sangkharak and Prasertsan 2012;Kumar et al 2013;etc.). The highest level of PHA accumulation reported so far is 88.7 wt% of dry cell by using B. licheniformis M2-12 (Sangkharak and Prasertsan 2013).…”
Section: Pha-producing Bacillusmentioning
confidence: 99%
“…A number of Bacillus species, but not all, can accumulate PHA in their cells under unbalanced growth conditions. The Bacillus species reported as native producers of PHA are as follows: (Yilmaz et al 2005;Kaynar and Beyatli 2009;Sangkharak and Prasertsan 2012;Kumar et al 2013;etc.). The highest level of PHA accumulation reported so far is 88.7 wt% of dry cell by using B. licheniformis M2-12 (Sangkharak and Prasertsan 2013).…”
Section: Pha-producing Bacillusmentioning
confidence: 99%
“…Further, Koller et al have suggested to link ecology with economy, because bacteria residing at ecological niches like estuarine sediments, marine microbial mats, rhizosphere, groundwater sediments and engineered ecosystems with fluctuating nutrient contents support the population actively involved in PHA accumulation to meet the metabolic energy requirements during starvation period and this concept can be implemented industrially to reduce the cost of biopolymers commercially with sustainable production processes (268). Therefore, it is economical to use naturally producing microorganism due to safety and constant productivity rate, and there is great potential for producing PHAs in low-cost substrates, which can reduce PHAs production costs, because the cost of substrate is the most important factor for PHAs production (269)(270)(271). Moreover, novel-constituent polymers will reduce the unfavorable characteristics of PHA.…”
Section: Economical Aspectsmentioning
confidence: 99%
“…From an economical point of view, the price of the product ultimately depends on the substrate (mainly carbon source) cost, PHA yield on the substrate and the efficiency of product formulation in the downstream processing (31,107). It is a prerequisite to standardize all the fermentation conditions, and physical and chemical parameters for the successful implementation of commercial PHA production systems (269)(270)(271)(272)(273). PHAs production costs can be reduced by several means, including the use of cheap substrates, such as whey, favored in countries with important dairy industries, or the enhancement of product yield, for example by using recombinant E. coli (7,35,267,274).…”
Section: Economical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Ghate et al [8] isolated different Bacillus species for the production of polyhydroxybutyrate (PHB) from soil samples. Sangkharak et al [9] isolated twenty five Bacillus sp. strains that were able to accumulate polyhydroxyalkanoates (PHAs).…”
Section: Introductionmentioning
confidence: 99%